THE CONCEPT OF QATH’I ACCORDING TO ASY-SYATIBI IN THE KITAB AL-MUWAFAQAT - Munadi Munadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
This topic is written because the concept of qath’i introduced by Ash-Syatibi as contained in his book al-Muwafaqat is different from that conceptualized by Jumhur scholars. According to ash-Syatibi, that all fundamental premises (muqaddimah) in legal theory must be something that is clearly certain (qath’i), and these premises can be rational, conventional or revelation. In his book it is explained that there is no or very little verse of the Qur'an that is qath’i, if what is meant there is no other possible meaning for a while. The concept of qath’i developed by Ash-Syatibi has contributed significantly to the development of the science of Usul fiqh. Methodologically, asy-Syatibi developed his legal theory through inductive reasoning (istiqra’) more broadly which was previously deductive. With the application of the induction method, the qath’i-an (certainty) of the meaning of a nashh is obtained through careful investigation of all Syar'i arguments that contain the same meaning so that the meaning is no longer zhanni but increases to mutawatir Ma'nawiyyah and is named qath’i al-Dilalah.